1977
DOI: 10.1084/jem.145.3.578
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the receptor for phage A25 in group A streptococci: the role of peptidoglycan in reversible adsorption.

Abstract: The first step in the life cycle of a bacteriophage is its attachment to an outer surface of the bacterial cell. In gram-positive bacteria the cell wall peptidoglycan, or this molecule complexed with other macromolecules, often serves as the phage receptor (1). Previous reports have suggested that the group-specific carbohydrate may play a role as receptor site for the virulent group A streptococcal phage, A25. The inhibition of adsorption by group A antisera and the inability of group A variant cells to adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

1978
1978
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…O-acetylation of the lipopolysaccharide side chains, changes in the bonding between the lipopolysaccharide trisaccharide units from a1A4 to b1A4) on the host cell, resulting in the inability of the cell to adsorb additional phage. Although the previous examples of phage receptor modification involve Gram-negative bacteria, it is possible that a similar phenomenon may occur in E. faecalis as the phage receptors in most Gram-positive, low G+C bacteria are cell surface polysaccharides (Vidaver & Brock, 1966;Douglas & Wolin, 1971;Cleary et al, 1977;Yokokura 1977;Keogh & Pettingill, 1983;Valyasevi et al, 1990;Schäfer et al, 1991). If this is the case, then evolutionarily speaking, it may be that originally E. faecalis TUSoD11 was nonlysogenic and possessed cell-surface phage receptors.…”
Section: Discussionmentioning
confidence: 99%
“…O-acetylation of the lipopolysaccharide side chains, changes in the bonding between the lipopolysaccharide trisaccharide units from a1A4 to b1A4) on the host cell, resulting in the inability of the cell to adsorb additional phage. Although the previous examples of phage receptor modification involve Gram-negative bacteria, it is possible that a similar phenomenon may occur in E. faecalis as the phage receptors in most Gram-positive, low G+C bacteria are cell surface polysaccharides (Vidaver & Brock, 1966;Douglas & Wolin, 1971;Cleary et al, 1977;Yokokura 1977;Keogh & Pettingill, 1983;Valyasevi et al, 1990;Schäfer et al, 1991). If this is the case, then evolutionarily speaking, it may be that originally E. faecalis TUSoD11 was nonlysogenic and possessed cell-surface phage receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The cell wall cross-bridges of these organisms are virtually identical (56), and it seems likely that the peptidoglycan structure is also similar. The muralytic lysin enzyme from phage A25 is active on the cell walls of group A, C, and G streptococci (22), and group A and C streptococci have been shown to possess the receptor for phage A25 (9). Similarly, group A and C streptococci are sensitive to the C1 phage lysin (45).…”
Section: Discussionmentioning
confidence: 99%
“…The streptococci used for these experiments were free of Fc-binding factor (Christensen et al, 1976), since the presence of Fc-binding factor disturbed the specificity of the antibody binding. By phage-adsorption experiments Cleary et al (1977) have shown that at least part of the peptidoglycan is located at the coccal surface. Similar results has been obtained by means of the immunofluorescence technique on B. licheniforrnis cells (Hughes & Stokes, 1971).…”
Section: Discussionmentioning
confidence: 99%